2019
DOI: 10.18764/2178-2865.v23n1p268-286
|View full text |Cite
|
Sign up to set email alerts
|

VIOLÊNCIA DE GÊNERO: expressões e vivências de mulheres brasileiras migrantes em Portugal

Abstract: O artigo traz considerações sobre a violência de gênero tendo em vista a apreensão de suas expressões e vivências em mulheres brasileiras que se encontram na condição de migrantes residentes em Portugal. Com base em aportes teóricos, documentais e empíricos, subsidiados por um estudo de caso realizado de janeiro a dezembro de 2019, discute o complexo fenômeno da migração e os desafios que imprime para as mulheres, dado que depende de uma série de condições materiais e sociais concretas, cujas ausências conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In Portugal, trafficking victims for the purpose of sexual exploitation were, in 2018, mostly from Brazil (Internal Security System, 2018). The study by Dias and Ramos (2019) on the expressions and experiences of gender violence in immigrant Brazilian women also por-trays this double condition of fragility, by reporting that 90.0% of these women have already suffered violence because they are women and immigrants.…”
Section: Antecedents For Understanding the Experience Of Violent Inti...mentioning
confidence: 99%
See 3 more Smart Citations
“…In Portugal, trafficking victims for the purpose of sexual exploitation were, in 2018, mostly from Brazil (Internal Security System, 2018). The study by Dias and Ramos (2019) on the expressions and experiences of gender violence in immigrant Brazilian women also por-trays this double condition of fragility, by reporting that 90.0% of these women have already suffered violence because they are women and immigrants.…”
Section: Antecedents For Understanding the Experience Of Violent Inti...mentioning
confidence: 99%
“…Several studies have concluded that Brazilian women in Portugal are particularly vulnerable to preconception, discrimination, racism, and sexism experiences, which come in forms of violent and unwanted physical sexual investments (Campos et al, 2018;Oliveira Assis, 2020;Dias & Ramos, 2019), both at public and private places (Piper et al, 2017;Premji & Shakya, 2017), that threaten, disturb, and intimidate these women, affecting their well-being and their sense of belonging to the Portuguese community (França & Padilla, 2018).…”
Section: Antecedents For Understanding the Experience Of Violent Inti...mentioning
confidence: 99%
See 2 more Smart Citations